ANALYSIS OF HADITH UNDERSTANDING OF SOCIAL MEDIA PHENOMENA AS A COMMUNICATION TOOL IN THE DIGITAL ERA - Daffa, Muhammad (RIWAYAH, 2022)
Social interaction is not only done face to face communication but also social interaction can be done online through the sophistication of information technology called social media. The development of social media is becoming a necessity in the 21st century. This research aims to analyze hadith understanding of social media phenomena as a communication tool in the digital era. The formulation of this research problem is how to understand hadith to the phenomenon of social media as a communication tool in the digital era. This study aims to discuss the analysis of hadith understanding of the phenomenon of social media as a means of communication in the digital era. This research is a literature study that focuses research on social media. This research study uses a qualitative approach by applying literature study methods. The formal object of this research is the science of hadith, while the material object is hadith against the phenomenon of social media as a means of communication in the digital era. The results showed that Tirmidhi Hadith Number 2432 contains the importance of good social interaction. Understanding hadith encourages good interaction with social media phenomena. As a means of communication in the digital age, social media has a good and bad influence on social change. This study recommends more in-depth hadith research into the phenomenon of social media.[Analisis Pemahaman Hadis Terhadap Fenomena Sosial Media sebagai Alat Komunikasi di Era Digital. Interaksi sosial tidak hanya dilakukan secara face to face communication, tapi juga interaksi sosial dapat dilakukan secara online melalui kecanggihan teknologi informasi yang disebut sosial media. Perkembangan penggunaan sosial media menjadi sebuah kebutuhan di abad ke-21. Penelitian ini bertujuan melakukan analisis pemahaman hadis terhadap fenomena sosial media sebagai alat komunikasi di era digital. Rumusan masalah penelitian ini adalah bagaimana pemahaman hadis terhadap fenomena sosial media sebagai alat komunikasi di era digital. Kajian ini bertujuan untuk membahas analisis pemahaman hadis terhadap fenomena sosial media sebagai alat komunikasi di era digital. Penelitian ini merupakan penelitian kepustakaan yang memfokuskan penelitian terhadap sosial media. Kajian penelitian ini menggunakan pendekatan kualitatif dengan menerapkan metode studi literatur. Objek formal penelitian ini adalah ilmu hadis, sedangkan objek materialnya hadis terhadap fenomena sosial media sebagai alat komunikasi di era digital. Hasil penelitian menunjukkan hadis Tirmidzi Nomor 2432 berisi tentang pentingnya interaksi sosial yang baik. Pemahaman hadis mendorong adanya interaksi yang baik terhadap fenomena sosial media. Sebagai alat komunikasi di era digital, media sosial memiliki pengaruh yang baik dan buruk terhadap perubahan sosial. Penelitian ini merekomendasikan penelitian hadis yang lebih mendalam terhadap fenomena media sosial.]